Regional economic outlook : Western Hemisphere - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
In the context of a still broadly favorable global environment, the economic outlook for the Western Hemisphere remains strong. Despite tighter monetary conditions, global growth is expected to be around 5 percent in 2006 and 2007, as a declaration of growth in the United States to about 21/2 percent in 2007 is offset by higher growth in the euro area and Japan, and continued high growth in emerging Asia. The Latin America and Caribbean region is expected to grow by 4 3/4 percent in 2006 - making the ongoing expansion the most vigorous for some decades -and by about 4 1/4 percent in 2007.
"November 2006."
Includes bibliographical references: p. 45-47.
rpm 17/08/2016
Loans
Keywords: Economic forecasting; Economic conditions; North America; Latin America; Caribbean Area